Environmental exposure does not explain putative maladaptation in road-adjacent populations. - Brady, Steven P (Oecologia, 2017)
While the ecological consequences of roads are well described, little is known of their role as agents of natural selection, which can shape adaptive and maladaptive responses in populations influenced by roads. This knowledge gap persists despite a growing appreciation for the influence of evolution in human-altered environments. There, insights indicate that natural selection typically results in local adaptation. Thus, populations influenced by road-induced selection should evolve fitness advantages in their local environment. Contrary to this expectation, wood frog tadpoles from roadside populations show evidence of a fitness disadvantage, consistent with local maladaptation. Specifically, in reciprocal transplants, roadside populations survive at lower rates compared to populations away from roads. A key question remaining is whether roadside environmental conditions experienced by early stage embryos induce this outcome. This represents an important missing piece in evaluating the evolutionary nature of this maladaptation pattern. Here, I address this gap using a reciprocal transplant experiment designed to test the hypothesis that embryonic exposure to roadside pond water induces a survival disadvantage. Contrary to this hypothesis, my results show that reduced survival persists when embryonic exposure is controlled. This outcome indicates that the survival disadvantage is parentally mediated, either genetically and/or through inherited environmental effects. This result suggests that roadside populations are either truly maladapted or potentially locally adapted at later life stages. I discuss these interpretations, noting that regardless of mechanism, patterns consistent with maladaptation have important implications for conservation. In light of the pervasiveness of roads, further resolution explaining maladaptive responses remains a critical challenge in conservation.
14 citations (Crossref) [2023-10-31] Place: Germany Brady, Steven P. School of Forestry & Environmental Studies, Yale University, 370 Prospect Street, New Haven, CT, 06511, USA. brady.steven@gmail.com. Brady, Steven P. Biology Department, Southern Connecticut State University, New Haven, CT, 06515, USA. brady.steven@gmail.com.
Keywords: *Adaptation; Physiological; *Environmental Exposure; *Ranidae; *Selection; Genetic; Acclimatization; Adaptation; Physiological; Amphibia; Amphibians; Animals; Contemporary evolution; Environmental Exposure; Inherited environmental effects; Larva; Local adaptation; Rana sylvatica; Ranidae; Ranidae/ph [Physiology]; Runoff; Selection; Genetic; acclimatization; adaptation; amphibian; animal; dept.bio; embryonic development; environmental conditions; environmental effect; environmental exposure; evolutionary biology; fitness; frog; genetic selection; larva; local adaptation; natural selection; physiology; pond; population type; roadside environment; runoff; survival

Positive sire effects and adaptive genotype by environment interaction occur despite pattern of local maladaptation in roadside populations of an amphibian - Brady, Steven P.; Goedert, Debora (Copeia, 2017)
The global road network causes many negative ecological effects. Contrasting our knowledge of these effects, insights into evolutionary consequences of roads remain undeveloped. Here, we study a suite of populations of the Wood Frog that appear to be evolving maladaptively in response to road-adjacency. Specifically, when raised together in roadside pools, roadside populations survive at lower rates compared to populations away from roads. To begin to understand the cause of this survival disadvantage, we investigated potential parental and genetic sources of maladaptation. First, to assess whether parental effects might induce maladaptation, we measured adult body weight to length ratio ('relative weight') and its influence on offspring survival in a reciprocal transplant experiment across 12 populations. Next, to assess whether genetic effects might limit adaptive responses in offspring, we estimated genetic correlations between environments for survival and fitness-related traits. We found that relative weight was higher in roadside populations and, for males, had a positive influence on offspring survival. This demonstrates a novel transgenerational effect of Wood Frog adult males but suggests that this effect is not causing maladaptive survival. Genetic correlations indicated that a subset of roadside genotypes respond adaptively to road-adjacency despite population level maladaptive survival. This suggests that metapopulation dynamics and/or high levels of nonadditive genetic variance may be limiting adaptation or that insufficient time has elapsed for adaptation to occur. Together, these results highlight the complexity and scale of responses to a pervasive feature of landscape alteration revealed by evolutionary approaches.
6 citations (Crossref) [2023-10-31]
Keywords: Amphibia; Rana sylvatica; adaptation; amphibian; dept.bio; environmental conditions; evolutionary biology; frog; genotype; genotype-environment interaction; heritability; local adaptation; metapopulation; population type; roadside environment; survival

Road ecology: shifting gears toward evolutionary perspectives - Brady, Steven P.; Richardson, Jonathan L. (Frontiers in Ecology and the Environment, 2017)
Recent advances in understanding the often rapid pace of evolution are reshaping our view of organisms and their capacity to cope with environmental change. Though evolutionary perspectives have gained traction in many fields of conservation, road ecology is not among them. This is surprising because roads are pervasive landscape features that generate intense natural selection. The biological outcomes from these selection pressures – whether adaptive or maladaptive – can have profound consequences for population persistence. We argue that studying evolutionary responses is critical to accurately understand the impacts of roads. Toward that end, we describe the basic tenets and relevance of contemporary evolution and showcase the few examples where it has been documented in road ecology. We outline practical ways that road ecologists can estimate and interpret evolutionary responses in their research. Finally, we suggest priority research topics and discuss how evolutionary insights can inform conservation in landscapes traversed by roads.
42 citations (Crossref) [2023-10-31]
Keywords: dept.bio; peer-reviewed

Incorporating evolutionary insights to improve ecotoxicology for freshwater species - Brady, Steven P.; Richardson, Jonathan L.; Kunz, Bethany K. (Evolutionary Applications, 2017)
Ecotoxicological studies have provided extensive insights into the lethal and sublethal effects of environmental contaminants. These insights are critical for environmental regulatory frameworks, which rely on knowledge of toxicity for developing policies to manage contaminants. While varied approaches have been applied to ecotoxicological questions, perspectives related to the evolutionary history of focal species or populations have received little consideration. Here, we evaluate chloride toxicity from the perspectives of both macroevolution and contemporary evolution. First, by mapping chloride toxicity values derived from the literature onto a phylogeny of macroinvertebrates, fish, and amphibians, we tested whether macroevolutionary relationships across species and taxa are predictive of chloride tolerance. Next, we conducted chloride exposure tests for two amphibian species to assess whether potential contemporary evolutionary change associated with environmental chloride contamination influences chloride tolerance across local populations. We show that explicitly evaluating both macroevolution and contemporary evolution can provide important and even qualitatively different insights from those obtained via traditional ecotoxicological studies. While macroevolutionary perspectives can help forecast toxicological end points for species with untested sensitivities, contemporary evolutionary perspectives demonstrate the need to consider the environmental context of exposed populations when measuring toxicity. Accounting for divergence among populations of interest can provide more accurate and relevant information related to the sensitivity of populations that may be evolving in response to selection from contaminant exposure. Our data show that approaches accounting for and specifically examining variation among natural populations should become standard practice in ecotoxicology.
34 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-040-409-668-282, pop00101 tex.type: [object Object]
Keywords: LC50; acute exposure; adaptation; chloride; dept.bio; maladaptation; peer-reviewed; road salt runoff

Evolutionary toxicology: Toward a unified understanding of life's response to toxic chemicals. - Brady, Steven P; Monosson, Emily; Matson, Cole W; Bickham, John W (Evolutionary Applications, 2017)
45 citations (Crossref) [2023-10-31] Place: England Brady, Steven P. Biology Department Southern Connecticut State University New Haven CT USA. Monosson, Emily. The Ronin Institute for Independent Scholars and Department of Environmental Conservation University of Massachusetts Amherst MA USA. Matson, Cole W. Department of Environmental Science and Center for Reservoir and Aquatic Systems Research (CRASR) Baylor University Waco TX USA. Bickham, John W. Department of Wildlife & Fisheries Sciences Texas A&M University College Station College Station TX USA.
Keywords: dept.bio; peer-reviewed

Physiological consequences of exposure to salinized roadside ponds on wood frog larvae and adults - Hall, Emily M.; Brady, Steven P.; Mattheus, Nichole M.; Earley, Ryan L.; Diamond, Molly; Crespi, Erica J. (Biological Conservation, 2017)
40 citations (Crossref) [2023-10-31]
Keywords: dept.bio